The Effect of SmallTalk2Me in English Instruction at MTs Pesantren Al-Amin Sooko Mojokerto - Wicaksono, Catur; Afidah, Nurul; Ma'arif, Iin Baroroh; Agustina, Ulfa Wulan (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This study aimed to assess the effectiveness of SmallTalk2Me as a learning tool, identify obstacles during its implementation, and investigate the role of SmallTalk2Me as an English speaking learning media at MTs Pesantren Al-Amin Sooko Mojokerto. This study used a mixed-methods approach, and data were collected from 26 male students through an English speaking test, observation, interviews, and questionnaires. The results showed a significant improvement in students' speaking skill, though the effectiveness was limited by technical challenges such as unstable internet and noise in the classroom. Students preferred a blend of AI tools and traditional teaching methods. The study highlighted the potential of SmallTalk2Me in enhancing English speaking but recommended addressing infrastructure issues and incorporating longer implementation periods. Further research was suggested to focus on the long-term impact of AI-powered tools in language learning. Keywords: SmallTalk2Me; AI; Speaking Skill; The Effect.